Does greater transparency discipline the loan loss provisioning of privately held banks? - Jannis Bischof; Daniel Foos; Jan Riepe (Deutsche Bundesbank, 2020)
We investigate the relationship between the transparency of loan loss provision disclosures and the provisioning practices of privately held banks. We study a unique change in disclosure regulation under German banking law which introduces mandatory disclosures of loan loss provisions. Using proprietary data provided by the national supervisor, we are able to observe provisioning practices before and after disclosure becomes mandatory. Our findings suggest that bank managers use loan loss provisions to a lesser extent for income smoothing once they are required to disclose their accounting choice. At the same time, provisions become more informative about future loan losses. The change comes in the absence of capital market pressure and highlights the role of depositors and public pressure in the monitoring of bank managers. We exploit cross-sectional variation and show that the change is associated with differences in the local information environment and banks' funding structure.
Keywords: G21; G28; M41; M48; 330; Loan Loss Provisions; Public Disclosure; Privately Held Banks; Earnings Smoothing; Market Discipline